Medical image : ROI and RONI definition using fuzzy logic - Song, Chia Yeh (2014)
This thesis discusses on the edge detection in fuzzy logic before medical image watermarking. Normally most of the researcher defined the ROT and RON! in the medical image manually. This research will be proposed that the ROl and ROM in the medical image can be defined automatically by using fuzzy logic. There are rules of inference in the FIS which will affect the relationship between the different variables of a fuzzy system input variable and fuzzy output. The images will be used to process are ultrasound, magnetic resonance imaging, computed tomography etc. Firstly, the area of interest (ROl) of the particular ultrasound image will be determined using fuzzy logic. 2x2 pixel window is used to determine whether the pixel is black, white or an edge. Then, we definitely know that which is the ROl and ROM in the ultrasound image by determining the edge using FIS. Thus, this will help doctor on determining the ROT which could be faster than doctor determined it one by one. Computational system should implement widely due to the increasing of medical image. After that, it will proceed with embed the watermark on the ROM by using least significant bit (LSB) technique or other techniques so that it can help in preserve imperceptibility of the watermarked image.